Optimisation of self-healing of bio-foamed concrete bricks pores using Bacillus tequilensis under different temperature and CO2 curing conditions - Abdullah F. Alshalif; M. Irwan Juki; Husnul Azan Tajarudin; N. Othman; Adel Ali Al-Gheethi; S. Shamsudin; Wahid Altowayti; Saddam Abo Sabah (Scientific Reports, 2022)
Abstract The self-healing of bio-concrete cracks and pores have been utilised worldwide to improve the properties of bio-concrete using different types of bacteria. Meanwhile, no published research was conducted to heal bio-foamed concrete bricks (B-FCB) pores using Bacillus tequilensis. Previous studies focused on the concentration of bacteria and neglect other factors that could affect the healing process. This research aimed to optimise the healing ratio of B-FCB pores using four factors: B. tequilensis concentration, concrete density, temperature and CO2 concentration. Initial water absorption (IWA) and water absorption (WA) were used as responses in statistical methods, namely, factorial and response surface methodology (RSM). B. tequilensis species was isolated from cement kiln dust, produced in a powder form, then subjected to simulate test using a special medium consisting of foamed concrete materials to check the survival ability in B-FCB. SEM, EDX, and XRD were used to investigate the healing process of B-FCB pores. The results revealed that the decrement ratios of IWA and WA of B-FCB were 52.8% and 29.1% compared to FCB, respectively. SEM results reflect the healing that occurred in B-FCB pores, mostly healed via precipitation of CaCO3 as demonstrated on the XRD results.